The Effects of Skill Variety, Task Significance, Task Identity and Autonomy on Occupational Burnout in a Hospital Setting and the Mediating Effect of Work Meaningfulness - Carrière, Jules; Bremner, Nicholas (Université d'Ottawa | University of Ottawa, 2011)
The relationships between four job characteristics, meaningful work, and burnout were examined. Meaningful work had a negative relationship with two dimensions of burnout and minimal mediation effects. Skill variety and task identity had direct effects on cynicism and professional efficacy, respectively. Results indicate that other factors must explain incremental variance of meaningful work.